Analysis of the Institutional Framework For Radioactive Waste Management in Indonesia - D.S. Wisnubroto (PPIKSN-BATAN, 2009)
The analysis of the infrastructure for radioactive waste management in Indonesia has been studied using several parameters, i.e. policy, regulatory authorities and their regulations, implementing organizations and financial system. By considering the international trends and the Indonesian program to utilize nuclear power, the infrastructure of radioactive waste management needs to be improved. The Act No. 10/1997 on Nuclear Energy for the future beneficence will have to be amended to incorporate several missing key points on waste management, such as definition of radioactive waste, disposal of Low and Intermediate Level Waste (LILW), and classification of waste. Full involvement of some important stakeholders, especially the State Ministry of Environment, on the radioactive waste management infrastructure is required since some radioactive waste is generated from non nuclear waste. Assigning full authority to the State Ministry of Environment for regulating radioactive waste generated by non nuclear facilities may be more effective, whereas BAPETEN is still holding onto control over the waste generated from nuclear facilities. In the near future, several regulations on clearance level, classification of waste, NORM/TENORM, and financial system are expected to be set up for urgent need. By considering the high risk for handling of radioactivity, including for transportation and storage, the liability or assurance of the safety for such activities must be accounted for. Finally, establishment of financial system for long term waste management in Indonesia needs to be implemented to ensure that the radioactive waste will not be the burden on future generations.Received: 21 April 2009; Revised: 18 August 2009; Accepted: 25 August 2009